Free-space NPR mode locked erbrium doped fiber laser based frequency comb for optical frequency measurement - Turghun, Matniyaz (Kansas State University, 2014)
This thesis reports our attempt towards achieving a phase stabilized free-space nonlinear polarization rotation (NPR) mode locked erbium doped fiber laser frequency comb system. Optical frequency combs generated by mode-locked femtosecond fiber lasers are vital tools for ultra-precision frequency metrology and molecular spectroscopy. However, the comb bandwidth and average output power become the two main limiting elements in the application of femtosecond optical frequency combs. We have specifically investigated the free-space mode locking dynamics of erbium-doped fiber (EDF) mode-locked ultrafast lasers via nonlinear polarization rotation (NPR) in the normal dispersion regime. To do so, we built a passively mode-locked fiber laser based on NPR with a repetition rate of 89 MHz producing an octave-spanning spectrum due to supercontinuum (SC) generation in highly nonlinear fiber (HNLF). Most significantly, we have achieved highly stable self-starting NPR mode-locked femtosecond fiber laser based frequency comb which has been running mode locked for the past one year without any need to redo the mode locking. By using the free-space NPR comb scheme, we have not only shortened the cavity length, but also have obtained 5 to 10 times higher output power (more than 30 mW at central wavelength of 1570 nm) and much broader spectral comb bandwidth (about 54 nm) compared to conventional all-fiber cavity structure with less than 1 mW average output power and only 10 nm spectral bandwidth. The pulse output from the NPR comb is amplified through a 1 m long EDF, then compressed by a length of anomalous dispersion fiber to a near transform limited pulse duration. The amplified transform limited pulse, with an average power of 180 mW and pulse duration of 70 fs, is used to generate a supercontinuum of 140 mW. SC generation via propagation in HNLF is optimized for specific polling period and heating temperature of PPLN crystal for SHG around 1030 nm. At last, we will also discuss the attempt of second harmonic generation (SHG) by quasi phase matching in the periodically polled lithium niobate (PPLN) crystal due to nonlinear effect corresponding to different polling period and heating temperature.
Keywords: Mode-locked laser; Frequency comb; Erbium doped fiber laser; Nonlinear polarization rotation; Phase stabilization; Ultra-short pulse; Engineering (0537); Optics (0752); Physics (0605)